Ask Question
5 November, 06:43

Let B = { (1, 3), (-2, - 2) } and B' = { (-12, 0), (-4, 4) } be bases for R2, and let A = 0 2 3 4 be the matrix for T: R2 → R2 relative to B.

(a) Find the transition matrix P from B' to B. P =

(b) Use the matrices P and A to find [v]B and [T (v) ]B, where [v]B' = [-2 4]T. [v]B = [T (v) ]B =

(c) Find P-1 and A' (the matrix for T relative to B'). P-1 = A' = (

(d) Find [T (v) ]B' two ways. [T (v) ]B' = P-1[T (v) ]B = [T (v) ]B' = A'[v]B' =

0
Answers (1)
  1. 5 November, 07:05
    0
    Step-by-step explanation:

    a) Let M =

    1 - 2 - 12 - 4

    3 - 2 0 4

    The RREF of M is

    1 0 6 4

    0 1 9 4

    Hence, the transition matrix P from B' to B is P =

    6 4

    9 4

    (b).

    Since [v]B' = (2 - 1) T, hence [v]B = P[v]B' = (8,14) T.

    (c).

    Let N = [P|I2] =

    6 4 1 0

    9 4 0 1

    The RREF of N is

    1 0 - 1/3 1/3

    0 1 ¾ - 1/2

    Hence, P^-1 =

    -1/3 1/3

    ¾ - 1/2

    Also, A' = PA =

    12 28

    12 34

    (d). [T (v) ]B' = A'[v]B' = (-4,10) T
Know the Answer?
Not Sure About the Answer?
Find an answer to your question ✅ “Let B = { (1, 3), (-2, - 2) } and B' = { (-12, 0), (-4, 4) } be bases for R2, and let A = 0 2 3 4 be the matrix for T: R2 → R2 relative to ...” in 📘 Mathematics if you're in doubt about the correctness of the answers or there's no answer, then try to use the smart search and find answers to the similar questions.
Search for Other Answers